DISTRIBUTION OF ROOT SYSTEM AT APPLE CV. GRANNY SMITH GRAFTED ON DIFFERENT DWARFING ROOTSTOCKS - Gjamovski, Viktor; Kiprijanovski, Marjan; Arsov, Tosho (Macedonian Academy of Sciences and Arts, 2018)
This paper analyses the distribution of root systems of nine dwarf apple rootstocks (M.9 T 984, M.9 T 337, Jork 9, Mark 9, Budagowski 9, M.9 EMLA, Pajam 1, Pajam 2 and Supporter 4). All rootstocks were grafted with apple cultivar Granny Smith. The study was performed in the experimental orchard established in the Prespa region (Resen, R. Macedonia). The experimental orchard was established in 2004, with a planting distance 3.5 m x 1.5 m. At the end of the 7th growing season following characteristics were evaluated: length and weight of the fine (fibrous) and coarse roots, and depth distribution of the root system. Among the evaluated rootstocks statistically significant differ-ences in total length of the fine roots were not found. Between different rootstocks the results for total length of coarse roots showed more variability. In general, even 89% of the total length of root system belonged to fine roots, and the highest percentage (35%) was located at depths of 20 to 40 cm. Trees grafted on Mark 9 rootstock had the highest value for total root length, while the smallest values were registered on those grafted on Pajam 1 rootstock. Trees grafted on Supporter 4 rootstock had the greatest weight of the root system, while the smallest one was found on rootstock Budagowski 9.